Training Interviewers to Spot ‘Faking’ in Employment Interviews: Can Frame of Reference Training Enhance Cue Detection, Cue Utilisation, and Overall Profile Accuracy for Rating Candidate Deceptive Impression Management? - Martin, Megan Anne (School of Management Studies, 2020)
Deceptive Impression Management (DIM), defined as faking in order to be perceived positively, is frequently used by candidates in employment interviews. DIM is problematic because it is difficult for interviewers to accurately rate, leading to unsound interview evaluations. This invalidates employment interviews because the best candidate is not selected for the job (i.e., deceptive candidates are hired above preferable honest candidates). Deceptive candidates’ good interview performance is negatively related to desired organisational outcomes (i.e., once hired, deceptive candidates are more likely to underperform on the job, as well as engage in undesirable workplace behaviours such as lack of effort and/or theft). Drawing on the Realistic Accuracy Model (RAM), it is argued that interviewers do not detect and/or utilise relevant and available DIM cues because they have not been taught to do so. The present study uses a post-test only true experimental design to determine whether students can be trained to accurately rate targets’ DIM. A Frame of Reference Training (FORT) intervention was developed, implemented, and evaluated. FORT aimed to teach experimental group participants to detect and utilise relevant and available DIM cues and to make accurate overall DIM profile ratings. Results show that FORT had a positive effect on DIM cue detection, but no effect on either DIM cue utilisation accuracy or overall DIM profile rating accuracy. Findings are attributed to the moderators of the ‘good judge’, ‘good information’ as well as the design and implementation of the FORT intervention. Because FORT had a positive effect on DIM cue detection accuracy, it is concluded that raters’ behaviour observation ability can be learned and improved with training. To the knowledge of the researcher and research supervisor, this is the first study to: (1) determine the trainability of DIM using FORT; (2) support and disentangle RAM by measuring the effect of FORT on each stage of RAM independently; (3) indirectly examine new dispositional reasoning schemas pertaining to DIM. Keywords: deceptive impression management (DIM), Frame of Reference training (FOR), Realistic Accuracy Model (RAM), accuracy, employment interviews.